When solving equations using addition, they will have the form x − b = c. Recall that ax + b = c is a linear equation.
Thus, the equation x − b = c is a linear equation with a = 1 and a negative sign in front of b.
To see this, notice that 1.x = x and − = + -
Thus, we can rewrite x − b = c as
1.x + -b = c
You can solve x − b = c in one step.
When solving one step equation of the form x − b = c, rewrite x − b = c as
x + -b = c and add b to both sides of the equation.
We will illustrate with two examples.
Example #1
Solve x − 2 = 8
Example #2
Solve x − 4 = -6
You could also solve the equation x - 4 = -6 as shown below as well.
x - 4 = -6
x + -4 = -6
x + -4 + 4 = -6 + 4
x + 0 = -2
x = -2
Related content:
Easily solve equations of the form x − b = c with the click of a button!
Jul 28, 17 02:38 PM
Bessy has 6 times as much money as Bob, but when each earn $6. Bessy will have 3 times as much money as Bob. How much does each have before and after
New math lessons
Your email is safe with us. We will only use it to inform you about new math lessons.
Jul 28, 17 02:38 PM
Bessy has 6 times as much money as Bob, but when each earn $6. Bessy will have 3 times as much money as Bob. How much does each have before and after